Pembuatan Media Animasi untuk Topik Hibridisasi dengan Program Macromedia Flash - Wijayanti, Fitria; S, Syukri; Yerimadesi, Yerimadesi (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2018)
Computer-based learning media can be one alternative in the learning of chemistry, especially hybridization concepts. This media will visualize abstract concepts into animations, drawings and help students understand concepts with interactive questions. The purpose of this research is to produce learning media on hybridization materials using macromedia flash program that can help the process of chemical learning. The type of research conducted is Research and Develompment (R & D). The instrument used is a questionnaire with Likert scale. The result of this research is hybridization learning media with macromedia flash program suitable to be used for science students at school.